In vivo characterization of the novel ebolavirus Bombali virus suggests a low pathogenic potential for humans - Bodmer, Bianca Susanne; Breithaupt, A.; Heung, M.; Brunetti, J. E.; Henkel, C.; Müller-Guhl, J.; Rodríguez, E.; Wendt, L.; Winter, Sophie L.; Vallbracht, Melina; Müller, A.; Römer, S.; et al. (Emerging Microbes & Infections, 2023)
Ebolaviruses cause outbreaks of haemorrhagic fever in Central and West Africa. Some members of this genus such as Ebola virus (EBOV) are highly pathogenic, with case fatality rates of up to 90%, whereas others such as Reston virus (RESTV) are apathogenic for humans. Bombali virus (BOMV) is a novel ebolavirus for which complete genome sequences were recently found in free-tailed bats, although no infectious virus could be isolated. Its pathogenic potential for humans is unknown. To address this question, we first determined whether proteins encoded by the available BOMV sequence found in Chaerephon pumilus were functional in in vitro assays. The correction of an apparent sequencing error in the glycoprotein based on these data then allowed us to generate infectious BOMV using reverse genetics and characterize its infection of human cells. Furthermore, we used HLA-A2-transgenic, NOD-scid-IL-2γ receptor-knockout (NSG-A2) mice reconstituted with human haematopoiesis as a model to evaluate the pathogenicity of BOMV in vivo in a human-like immune environment. These data demonstrate that not only does BOMV show a slower growth rate than EBOV in vitro, but it also shows low pathogenicity in humanized mice, comparable to previous studies using RESTV. Taken together, these findings suggest a low pathogenic potential of BOMV for humans.
Gesehen am 15.11.2023